2001
DOI: 10.1076/ceyr.23.2.77.5471
|View full text |Cite
|
Sign up to set email alerts
|

Corneal stimulation of MMP-1, -9 and uPA by platelet-activating factor is mediated by cyclooxygenase-2 metabolites

Abstract: During corneal injury and inflamation, PAF is an important factor in the activation of proteolytic cascades, which could lead to corneal epithelial defects and ultimately ulceration. One important goal in treating these defects is to modulate the activity of enzymes that destroy the extracellular matrix. Our results suggest that COX-2 induction following PAF stimulation and subsequent eicosanoid release may play a crucial role in the induction of uPA, MMP-1 and MMP-9 enzymes. Specific COX-2 inhibition could th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 15 publications
2
36
0
1
Order By: Relevance
“…25,26 Platelet activating factor-induced COX-2 upregulation is believed to be involved in the activation of matrix metalloproteinases MMP-1 and MMP-9, which are responsible for collagenolytic damage and ultimately for ulcer formation. 27,28 Increased expression of COX-2 and MMP-9 has been documented in DE. 4 Thus, testing potential drugs in the currently used model should give valuable insights to their potential clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Platelet activating factor-induced COX-2 upregulation is believed to be involved in the activation of matrix metalloproteinases MMP-1 and MMP-9, which are responsible for collagenolytic damage and ultimately for ulcer formation. 27,28 Increased expression of COX-2 and MMP-9 has been documented in DE. 4 Thus, testing potential drugs in the currently used model should give valuable insights to their potential clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that PAF regulates the activity of various MMPs in different cell types, including stimulation of the MMP-9 expression in corneal myofibroblasts (63), COX-2-mediated transactivation of urokinase plasminogen activator and MMP-1 and -9 in corneal cultures (64), and NFB-dependent expression of MMP-9 in endothelial ECV304 cells (65). Most recently, Axelrad et al (66) showed that PAF induced the transactivation of MT1-MMP and TIMP2 genes and the activation of MMP-2 in human umbilical vein endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, COX-2 induction and prostaglandin synthesis mediate the stimulation of uPA, MMP-1, and MMP-9 activity by PAF in rabbit corneas ( 65 ). Interestingly, the release of AA after cPLA2 stimulation induced by PAF does not increase the synthesis of 12(S)-HETE in rabbit corneal epithelia ( 42,43 ).…”
Section: Lipids In Corneal Pathologiesmentioning
confidence: 94%
“…PGF2 ␣ -isopropyl ester (latanoprost), a derivative of PGF2 ␣ , is commonly used as a potent ocular hypotensive drug in the management of glaucoma ( 62 ); however, glaucomatous patients often need to use these types of drugs for extensive periods, and some adverse effects have been reported. In a rabbit model of acute herpetic keratitis, latanoprost increases the severity and recurrence of this infection ( 63 ) ( 65,66 ).…”
Section: Lipids In Corneal Pathologiesmentioning
confidence: 99%